Peran Keputusan Bendahara Badan Perencanaan Pembangunan Daerah (Bappeda) Terhadap Dana Lembur Di Kantor Walikota Medan - Ummi Rahayu Saragih; Nurlaila Nurlaila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this research is to determine the role of the Bappeda treasurer's decisions regarding overtime funds. This research uses qualitative methods with process analysis and inductive thinking related to the dynamics of the relationship between the symptoms studied, while still using scientific thinking. By using descriptive methods. The treasurer has the task of carrying out some of the secretary's duties within the scope of financial administration management. The role of the Treasurer or finance sub-division is very much needed in disbursing overtime funds. And these overtime funds are issued by fulfilling several conditions that have been written down.